Low Prevalence of Thrombosis Prophylaxis Dose Adjustments Highlights Implications for Patient Safety - W. Anthony Hawkins; Susan E. Smith; Tia M. Stitt; Aliya Abdulla; Trisha N. Branan; Ronald G. Hall (University of Minnesota Libraries Publishing, 2021)
Background: Pharmacologic thromboprophylaxis (PTP) is the mainstay prevention strategy for venous thromboembolism (VTE). PTP agents traditionally dosed, like unfractionated heparin (UFH) and enoxaparin (ENOX), are associated with failure and bleeding in obese and underweight patients, respectively. Objectives: This study aimed to describe the prevalence of unadjusted ENOX and UFH dosing for PTP based on anthropometric measures. Patients/Methods: This was a post-hoc, multicenter, cross-sectional analysis of critically ill adults receiving PTP with ENOX or UFH. The primary outcome was the prevalence of unadjusted PTP based on body mass index (BMI) and total body weight (TBW). Definitions for dose adjustments were developed based on existing literature. A secondary outcome was to identify factors associated with unadjusted dosing per BMI and TBW using multivariable generalized linear mixed-effect models. Results: The nested cohort included 172 patients (ENOX=46, UFH=126). Unadjusted PTP was observed in 118 patients (68.6%) based on BMI and 74 (43%) per TBW. When comparing UFH to ENOX, more patients who received UFH had doses unadjusted by BMI (78.6% vs. 41.3%, p<0.05) but not TBW (43.7% vs. 41.3%). Factors independently associated with unadjusted PTP per BMI were receipt of UFH (OR 6.93, 95% CI 1.06-8.77) or a BMI underweight or overweight/obese (OR 10.45, 95% CI 4.38-24.92). Having a TBW <50kg or >100kg (OR 4.85, 95% CI 2.15-10.96) were independently associated with unadjusted PTP based on TBW. Conclusions: Unadjusted dosing of PTP occurs frequently in critically ill adults receiving ENOX or UFH. This was seen in body size extremes by both BMI and TBW.